Elucidating the surface geometric design of hydrophobic Australian Eucalyptus leaves: experimental and modeling studies. Issue 3 (March 2019) - Guo, Hua; Xie, Zonghan; Shaw, Jeremy; Dixon, Kingsley; Jiang, Zhong-Tao; Yin, Chun-Yang; Liu, Xuemei
Abstract: Three Australian native Eucalyptus species, i.e., Eucalyptus woodwardii, Eucalyptus pachyphylla and Eucalyptus dolorosa, were investigated, for the first time, with respect to the hydrophobicity of their leaves. It is well established that these leaves exhibit exceptionally high water repellency, in addition to an extraordinary ability to retain water, albeit their specific wetting mechanisms are still poorly understood. To identify the critical factors underlying this phenomenon, the surface topography of these leaves was subjected to micro-examination (SEM). Micro- and nanometer scale surface roughness was revealed, resembling that of the quintessential "lotus effect". Surface free energy analysis was performed on two models based on the surface topographies of the study Eucalyptus species and lotus, in order to study wetting transitions on these specific microscopic surface features. The influence of surface geometrical parameters, such as edge-to-edge distance, base radius and cylindrical height, on surface free energy with different liquid penetration depths was studied with these two models. Larger energy barriers and smaller liquid-solid contact areas were more influential in the calculations for the lotus than for Eucalyptus . The information obtained from these two models may be useful for guiding the design of novel artificial surfaces in the collection and transport of micro-volume liquids.